Manusia dalam Pandangan Ali Syariati dan Abdurrahman Wahid: Studi Filsafat Manusia - Rizki Mohammad Kalimi (Jurnal Penelitian Ilmu Ushuluddin, 2022)
At this time, human problems and all things related to it, more and more diverse. Unfortunately, science and technology, which were originally expected to provide a solution to these problems, have instead become a source of new problems. On the other hand, humans who are equipped with reason to think and ask questions, constantly try to explore the meaning of the mystery of who he is. Many thinkers have contributed their thoughts on the concept of man, but of these, it gives the impression that the deeper the meaning of man is dug, the more the basis for this search will not be found. This study aims to examine further the meaning of humans, so that by revealing the meaning of humans, humans can answer complex problems in themselves. The research method used is a qualitative method, based on the primary books of the characters being studied, and secondary data that supports these primary sources. This research resulted in a finding that humans have an essence where it is this essential thing that ultimately makes a person truly human.